Swine as the Animal Model for Testing New Formulations of Anti-Inflammatory Drugs: Carprofen Pharmacokinetics and Bioavailability of the Intramuscular Route (2022)
Carprofen (CP) is a non-steroidal anti-inflammatory drug (NSAID) frequently used to treat respiratory diseases in numerous small animals, but also in large species. CP is a formidable candidate for further therapeutic research of human inflammatory diseases using the pig as an animal model. However, CP administration in swine is very uncommon and respective pharmacokinetics/bioavailability studies are scarce. A simultaneous population pharmacokinetic analysis after CP intravenous and intramuscular administrations in pigs has shown high extent and rate of absorption and a similar distribution profile with respect to man and other mammals. However, clearance and half-life values found in swine suggest a slower elimination process than that observed in man and some other animal species. Although not reported in other species, liver and kidney concentrations achieved at 48 h post-intramuscular administration in pigs were ten times lower than those found in plasma. Simulations pointed to 4 mg/kg every 24 h as the best dosage regimen to achieve similar therapeutic levels to those observed in other animal species. All these findings support the use of pig as an animal model to study the anti-inflammatory effects of CP in humans.